Calcium foliar fertilization and its effect on quality and shelf life in andean blackberry fruits (Rubus glaucus Benth.) (2023)
Calcium is the third most crucial nutrient for andean blackberry; however, its absorption is limited in acid soils, and its low mobility in the plant decreases its effects on fruits. Therefore, the effect of foliar fertilizers with calcium on andean blackberry fruits was estimated. In three locations, experiments were established with five calcium sources (Ca chelate, CaB nitrate, Ca oxide, CaB and CaBZn gluconate) and a control without calcium, applied in three phenological stages and recording: weight, diameters, firmness, color, juice, pulp, pH, soluble solids, acidity, dehydration, and damage. Soil and tissue analysis was performed to identify the relationship between the plant's nutritional conditions and its fertilization response. For the statistical analysis were used mixed models, tests of means, and principal components. Foliar fertilization with chelate, nitrate, and calcium oxide in andean blackberry crops with thorns, in production, with pruning management, and in the phenological stages of flower bud, fruit set, and red fruit, is a viable alternative to improve firmness, weight, and diameter of the fruits. In contrast, the chemical and color parameters in andean blackberry fruits depend on the edaphoclimatic conditions of each zone. This fertilization should be considered as a complement in soils without acidity problems and with balanced cationic saturations.